Genetic Improvement of Dalbergia Species: Problems and Strategies - Mandal, A. K.; Subramanian, K. N.; Nagarajan, B. (Indian Forester, 1994)
Dalbergia latifolia and Dalbergia sissoo are two of the important timber yielding leguminous trees of India. They are known to occur in decidnous and mixed deciduous forests. They are well adapted to water clogged soil. Both the species are very well known for their coppicing nature which indirectly helps in the propagation of the species. Not much information is available on the genetics, breeding, floral biology aspects of the species. Biotechnological manipulation in terms of tissue culture and protoplast studies have been made and both species have responded positively. It is emphasised that further approaches in disciplines such as cytogenetics, genetics, breeding and biotechnology shall pave the way for betterment of the species.